Synthetic Fuels in a Transport Transition: Fuels to Prevent a Transport Underclass - Styring, Peter; Duckworth, Emily L.; Platt, Edward G. (Frontiers in Energy Research, 2021)
The Paris Agreement set policy scenarios to address mitigating against the climate emergency, by reducing greenhouse gas emissions to limit the temperature increase to 1.5°C. There has been a drive toward electrifying transport, with battery electric vehicles (BEVs) at the forefront. Reliance on single-technology policy development can lead to consequential impacts, often not considered, or dismissed. Energy cannot be created or destroyed but can be transformed. While BEVs may represent zero tailpipe emissions, the battery energy must be sourced elsewhere. An ideal policy scenario will come from “renewable” sources; however, current global energy mixes require the electricity to come from carbon-burning point source emitters. Therefore, the emissions are deferred to low socioeconomic regions. The move to ban new internal combustion engine (ICE) vehicle sales has been accelerated. High BEV costs will preclude low-income groups from making purchases. Such groups typically rely on used cars for mobility. Without considered consequential policy analysis, transport underclasses may result, where private transport is only accessible by the wealthy. Synthetic fuels derived from CO2 represent a social bridge in the energy transition, also helping to accelerate toward net zero. The Covid-19 lockdown provided a unique opportunity to experience an environment with reduced transport-related emissions. Global studies allowed the consequential effects of pollution reduction to be studied. These are surprising and offer the opportunity for policies, driven by science, to be developed. Here, we consider the consequential effects of clean air policies, and how these can be used to propose dynamic responses to policy recommendations.